Breaking fast with mentee: making memories during Buka Puasa / Suhaida Halamy - Halamy, Suhaida (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
From the beginning, I have never had the opportunity to teach them in person since Semester 1. Our interactions took place exclusively online. Instead, I relied on gossip and rumors from other lecturers who had taught them before, offering positive and negative feedback about their attitudes and academic performance. The absence of faceto- face contact left me unsatisfied, yearning to connect with my students truly. Finally, when they reached Semester 5, I seized the chance to teach them directly and observe their progress. The anticipation was palpable as I eagerly awaited their performance. Most of them excelled, shining brightly in their studies, to my delight. Witnessing their achievements filled me with pride and joy. However, some still needed more effort to reach their full potential. Nonetheless, the experience of finally being able to guide and instruct them in person was invaluable. It deepened our connection and reinforced the importance of nurturing each individual's growth. I encouraged and supported them with renewed determination as they embarked on their academic journey toward a brighter future.